(untitled) (Penerbit UTHM, 2026)
Water engineering: issues and management (series 3) consist of six chapters. Chapter 1 highlights how are of catchment influence peak runoff. This is because the delineation of water catchment can vary between methods used. The study examines the catchment of a residential area in Yong Peng, Johor. In Chapter 2, samplers are designed for macroinvertebrates sampling. These samplers are tested at the Ulu Dengar River and Gunung Belumut waterfalls, with the results presented in this book. Meanwhile, Chapter 3 focuses on the development of the calibration curve between phosphorus concentration and resistivity value. The experiments were carried out in laboratory in alkaline conditions. Chapter 4 reviews on the various methods of AN treatment in lakes in Malaysia. Advantages and disadvantages between physiochemical and biological process treatments were discussed. Chapter 5 presents results of site investigations at the coasts of Tanjung Laboh, Johor. Correlation between dept of seawater and coastal defense structure are studied for the purpose of mangrove rehabilitation. In the final chapter of the book, i.e. Chapter 6, the effectiveness of composite porous concrete slab as drain cover is reported. Experiments of the composite porous concrete (CPC) slab were conducted on site, and the results are reported here.